Promotion Mix Solusi Untuk Meningkatkan Keputusan Pembelian - Aisyah, Anni; Wibowo, Lili Adi; Widjajanta, Bambang (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2019)
The purpose of this research is to find out the influence of Â promotion mix toward purchase decision on wuling confero users in Indonesia. This research used cross sectional method and descriptive approach with survey explanatory method, and the sampling is 106 respondent. The result of research indicate that the promotion mix in good category and purchase decision in the good category. The data analysis technique used to find out the correlative relationship in this study is path analysis. To test the hypothesis, where the method of analysis carried out in this quantitative research is the verification analysis method, path analysis is carried outIn the research finding if the conditions of the promotion mix is good, the it will increase purchase decision